(untitled) (Journal of actual problems of jurisprudence, 2019)
In the final discussion of the results of the seminar, recommendations on the establishment of The Eurasian coordinating Council of ombudsmen, through which to exchange experience, theoretical development and analysis of practical activities of defenders of the rights of citizens. There was General agreement on the need for close international cooperation national human rights institutions in the field of monitoring the observance of the rights of citizens and application of generally recognized norms and standards in this field.